Effect of Storage Temperature on the Shelf Life of Self-adhesive Resin Cements - İRİBOZ, EMRE; SINMAZIŞIK, GÜLDEN; SAZAK ÖVEÇOĞLU, HESNA (QUINTESSENCE PUBLISHING CO INC, 2015)
Purpose: To compare the bonding performance of three new self-adhesive resin cements to human dentin after storage under two different conditions. Materials and Methods: Buccal, lingual, mesial, and distal dentin surfaces of 36 human molars were abraded to directly below the enamel with #600 SiC papers. The teeth were divided into two main test groups. In the first test group (FT), the cements were kept in a refrigerator (6 +/- 2 degrees C) for three months and then used for the test. The remainder of the cements was kept at a constant room temperature of 19 +/- 2 degrees C for an additional three months, and then used again for the second test group (ST). Each test group comprised 6 teeth and 24 dentin sections. The cements Clearfil SA (CSA), G-Cem (GC), and Bis-Cem (BC) were applied to the surfaces according to the manufacturers' recommendations. After application of the cements to the flat dentin surfaces and light curing, shear bond strengths were determined at a crosshead speed of 0.5 mm/min. Bond strengths were then calculated and expressed in MPa. Data were analyzed with Kruskal-Wallis and Wilcoxon Signed Rank tests. To investigate the cement/dentin interfaces using SEM, the buccal surfaces of three additional teeth were used for each test group. Results: The bond strength values of cement groups were significantly different for the FT and ST groups (p < 0.01). GC showed the highest bond strength values of all materials. There was a difference between the bond strength values of the two testing periods for all materials (p < 0.01). Bond strengths significantly decreased after storage at room temperature. Conclusion: Storage temperatures considerably affect the shelf life of self-adhesive resin cements.
Keywords: Clearfil SA; Bis-Cem; G-Cem; SEM; shelf life; storage time; SHEAR BOND STRENGTH; ETCHING PRIMER; HYDROLYTIC STABILITY; MECHANICAL-PROPERTIES; FUNCTIONAL MONOMERS; DENTIN; SYSTEMS; PERFORMANCE; ENAMEL; METHACRYLAMIDE